Women & music : a history - Pendle, Karin, 1939-2020 (Indiana University Press, 1991)
"Women and Music: A History is a survey of women's activities in music performance, composition, teaching, and patronage from the times of the ancient Greeks to the present, with an emphasis on art music in Europe and the Americas"--Preface.